Jamming the Classroom Musical Improvisation and Pedagogical Practice - Heble, Ajay (Music and Social Justice, 2023)
Drawing on a mix of collaborative autoethnography, secondary literature, interviews with leading improvisers, and personal anecdotal material, Jamming the Classroom discusses the pedagogy of musical improvisation as a vehicle for teaching, learning, and enacting social justice. Heble and Stewart write that to "jam the classroom" is to argue for a renewed understanding of improvisation as both a musical and a social practice; to activate the knowledge and resources associated with improvisational practices in an expression of noncompliance with dominant orders of knowledge production; and to recognize in the musical practices of aggrieved communities something far from the reaches of conventional forms of institutionalized power, yet something equally powerful, urgent, and expansive. With this definition of jamming the classroom in mind, Heble and Stewart argue that even as improvisation gains recognition within mainstream institutions (including classrooms in universities), it needs to be understood as a critique of dominant institutionalized assumptions and epistemic orders. Suggesting a closer consideration of why musical improvisation has been largely expunged from dominant models of pedagogical inquiry in both classrooms and communities, this book asks what it means to theorize the pedagogy of improvised music in relation to public programs of action, debate, and critical practice.